Nano Online 2016
DOI: 10.1515/nano.11671_2015.58
|View full text |Cite
|
Sign up to set email alerts
|

Study on adsorption and desorption of ammonia on graphene

Abstract: The gas sensor based on pristine graphene with conductance type was studied theoretically and experimentally. The time response of conductance measurements showed a quickly and largely increased conductivity when the sensor was exposed to ammonia gas produced by a bubble system of ammonia water. However, the desorption process in vacuum took more than 1 h which indicated that there was a larger number of transferred carriers and a strong adsorption force between ammonia and graphene. The desorption time could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…While such processes may explain the action of the adsorbates as charge donors or acceptors, 3 the calculations do not explain the new peak that water induces in the carbon-projected density of states as reflected in the carbon K edge absorption spectrum, Figure 1e,f. Regarding ammonia adsorption, similar conclusions about a lack of electronic state mixing were reached by Zhang and coworkers; 13 however, Leenarts et al 8 found a small charge transfer in DFT calculations of ammonia on graphene and concluded that donation from the 3a 1 orbital and backdonation into the 4a 1 may occur, in line with our above observations. Note that our temperature-programmed desorption experiments (ref 26; an example is given in Figure S3) suggest a much higher binding energy (∼450 meV), in line with results from Standop et al 42 The clustering observed by these authors for water on graphene/Ir(111) is not thought to affect our interpretation of the NEXAFS data because the clusters are planar.…”
supporting
confidence: 89%
“…While such processes may explain the action of the adsorbates as charge donors or acceptors, 3 the calculations do not explain the new peak that water induces in the carbon-projected density of states as reflected in the carbon K edge absorption spectrum, Figure 1e,f. Regarding ammonia adsorption, similar conclusions about a lack of electronic state mixing were reached by Zhang and coworkers; 13 however, Leenarts et al 8 found a small charge transfer in DFT calculations of ammonia on graphene and concluded that donation from the 3a 1 orbital and backdonation into the 4a 1 may occur, in line with our above observations. Note that our temperature-programmed desorption experiments (ref 26; an example is given in Figure S3) suggest a much higher binding energy (∼450 meV), in line with results from Standop et al 42 The clustering observed by these authors for water on graphene/Ir(111) is not thought to affect our interpretation of the NEXAFS data because the clusters are planar.…”
supporting
confidence: 89%
“…Figure b depicts the heat of adsorption for all NH 2 –UiO-66 variants which are in good agreement with experimental work on NH 2 –UiO-66 by Wiersum et al and are again driven up by the AA functionalization . The large spatial extent of lysine and tryptophan resulted in the largest increase in Q st , because of the significantly larger fraction of CO 2 molecules which are adsorbed in the primary layer of the host framework (indicated by the type I adsorption isotherm) . The same reasoning follows for the increase in CO 2 /N 2 selectivity, whereby with an increase in pressure, we see that the small AAs have significantly reduced selectivity compared with that of the larger lysine and tryptophan, for example with lysine having a selectivity of 27.4 compared with 22.4 of glycine at 70 kPa (Figure d).…”
supporting
confidence: 86%
“…As also discussed by Kang et al, 49 the surface dangling Si−O−H bonds on the polymer chains mediate the interactions to graphene sheets and induce electron doping via charge transfer. On the other hand, ammonia molecules can be adsorbed onto the graphene layers with small binding energy, 50 inducing a quicker cross-link creation. The rapid desorption kinetics of NH 3 in the Si−OH/graphene interface from the top surface and a much slower removal from the bottom surface of graphene at the interface 51 induces ordered and fast gelation and cross-linking reactions at the top interface of graphene with polymer chains.…”
Section: Resultsmentioning
confidence: 99%